DETERMINAN TINGKAT KKECEMASAN DENGAN INTENSITAS NYERI PADA PASIEN PRE OPERASI MAYOR DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Yoslin, Tricia Margaretha; Wijayanti, MI Ekatrina; Wibowo, Tandean Arif; Andiyan, Andiyan (Edu Masda Journal, 2024)
Major surgery is the most common surgical procedure and uses general anesthesia. The objective of this study was to determine the relationship between anxiety levels and pain intensity in pre-major surgery patients at Panti Rapih Hospital, Yogyakarta. The type of research used is quantitative research with a correlative analytical-descriptive research design with a cross-sectional approach. The sample obtained during the research was 37 patients. Data collection used purposive sampling and accidental sampling techniques. The results of the univariate test showed the patient's age characteristics; it was found that almost half (32.4%) were aged 18–28 years and also 51–70 years. The distribution of gender characteristics shows that the majority (59.5%) are female. In pre-major surgery patients, the majority (59.5%) will undergo laparotomy surgery. The level of anxiety in patients pre-major surgery was high; almost the majority (64.8%) experienced moderate anxiety. In pre-major surgery patients, almost half (48.6%) experienced moderate pain. This research used the Spearman correlation test. There is a significant relationship between anxiety level and pain intensity with a p value 0.011 and a correlation value of 0.411, which means there is a significant and positive relationship between variables. Suggestions for further research will continue similar research so that, in the future, they can increase the number of samples and types of major operations so that they can represent the population in order to get more ideal results.Abstrak Bedah mayor adalah prosedur bedah yang yang paling umum dan menggunakan anatesi general. Tujuan dari penelitian ini adalah untuk mengetahui hubungan tingkat kecemasan dengan intensitas nyeri pada pasien pre operasi mayor di rumah sakit Panti Rapih Yogyakarta. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian deskriptif analitik korelatif dengan pendekatan cross sectional. Sampel yang didapat saat penelitian ada sejumlah 37 pasien, pengambilan data menggunakan teknik purposive sampling dan accidental sampling. Hasil penelitian uji univariat mendapatkan hasil karakteristik usia pasien, diketahui hampir setengahnya (32.4%) berusia 18-28 tahun dan juga 51-70 tahun, Sebagian besar (59.5%) berjenis kelamin perempuan. Jenis operasi pada pasien pre operasi mayor, sebagian besar (59.5%) akan menjalani operasi laparotomi. tingkat kecemasan pada pasien pre operasi mayor, hampir sebagian besar (64.8%) mengalami kecemasan sedang. Intensitas nyeri pada pasien pre operasi mayor, hampir setengahnya (48.6%) mengalami nyeri sedang.  Penelitian ini menggunakan uji korelasi spearman, terdapat hubungan yang signifikan antara tingkat kecemasan dengan intensitas nyeri dengan p value 0.011 dan nilai korelasi 0.411, yang berarti adanya hubungan yang signifikan dan positif antar variable. Saran untuk penelitian selanjutnya adalah diharapkan bagi peneliti lain agar kedepannya bisa menambahkan jumlah sampel dan jenis operasi mayor agar bisa mewakili populasi agar mendapatkan hasil yang lebih ideal.